Inflammatory Bowel Disease in Women of Reproductive Age: Short and Long-Term Effect on Reproductive Health - Dani S. Mulyono (Academic Journal of Clinicians, 2025)
Inflammatory bowel diseases affect mainly young people during their social and professional activity, when they start a family and plan to have children. The relevance of this problem is also determined by the fact that in the last three decades there has been a high increase in the incidence of UC and CD, especially among young people. This is confirmed by the results of large controlled studies conducted in the UK, Sweden, Ireland, Denmark, according to which over the last decade the incidence of UC and CD has increased 3-fold and reached 225 per 100,000 population. The prevalence was 300 per 100,000 and was distributed equally between both diseases. Information on the prevalence of UC and CD in Russia is very scarce. According to published summary data, it is only known that out of 1,000 patients hospitalized in specialized gastroenterology clinics, 7 suffer from UC. From 1981 to 2000. An attempt was made to conduct epidemiological studies on IBD in the Moscow region. The results of the authors' work indicate a high percentage of severe and moderate forms of inflammatory bowel disease (IBD) in this region (UC-73%, BK-75%). It is important to note that the peak incidence of UC and CD occurs in the age group from 20 to 40 years. Considering that patients suffering from this pathology are mainly of reproductive age, studies aimed at developing tactics for managing women of reproductive age suffering from IBD and their treatment during pregnancy planning, during pregnancy and after childbirth are urgently needed.